Laboratory study of acoustic velocity in different types of rocks at seismic frequency band - He, Yunlan; Peng, Suping; Du, Wenfeng; Tang, Xiaoming; Zeng, Hu (Penerbit Universiti Kebangsaan Malaysia, 2017)
In order to understand the characteristics of acoustic wave propagation in rocks within seismic frequency band (<100 Hz), the velocities of longitudinal and transverse waves of four different types of rocks were tested using low-frequency stress-strain method by means of the physical testing system of rock at low frequency and the experimental data of acoustic velocities of four different types of rocks at this frequency band were obtained. The experimental results showed that the acoustic velocities of four different types of rocks increased with the increase of temperature and pressure within the temperature and pressure ranges set by the experiment. The acoustic velocity of fine sandstone at 50% water saturation was smaller than that of dry sample. The acoustic velocities of four different types of rocks were different and the velocities of longitudinal waves of gritstone, fine sandstone, argillaceous siltstone and mudstone increased in turn under similar conditions and were smaller than those at ultrasonic frequency. Few of existing studies focus on the acoustic velocity at seismic frequency band, thus, further understanding of the acoustic characteristics at this seismic frequency band still requires more experimental data.